2007
DOI: 10.1104/pp.106.091736
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Cycling in Anabaena sp. PCC 7120. Sucrose Synthesis in the Heterocysts and Possible Role in Nitrogen Fixation

Abstract: Nitrogen (N) available to plants mostly originates from N 2 fixation carried out by prokaryotes. Certain cyanobacterial species contribute to this energetically expensive process related to carbon (C) metabolism. Several filamentous strains differentiate heterocysts, specialized N 2 -fixing cells. To understand how C and N metabolism are regulated in photodiazotrophically grown organisms, we investigated the role of sucrose (Suc) biosynthesis in N 2 fixation in Anabaena sp. PCC 7120 (also known as Nostoc sp. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 64 publications
4
94
0
Order By: Relevance
“…This organism, which belongs to one of the first prokaryotic groups on earth to have evolved multicellularity, had to develop structures for intercellular communication. Intercellular communication between heterocysts and vegetative cells comprises small molecules, such as sucrose moving from vegetative cells to heterocysts (2)(3)(4)(5) and a dipeptide, β-aspartyl-arginine, moving from heterocysts to vegetative cells (6,7). The mechanism of communication between heterocysts and vegetative cells has been debated for the last 50 y.…”
mentioning
confidence: 99%
“…This organism, which belongs to one of the first prokaryotic groups on earth to have evolved multicellularity, had to develop structures for intercellular communication. Intercellular communication between heterocysts and vegetative cells comprises small molecules, such as sucrose moving from vegetative cells to heterocysts (2)(3)(4)(5) and a dipeptide, β-aspartyl-arginine, moving from heterocysts to vegetative cells (6,7). The mechanism of communication between heterocysts and vegetative cells has been debated for the last 50 y.…”
mentioning
confidence: 99%
“…Although UDP is generally considered to be the preferred nucleoside diphosphate for SUS, numerous studies have shown that ADP serves as an effective acceptor molecule to produce ADP-glucose (ADPG) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). SUS is highly regulated both at transcriptional and posttranslational levels (15)(16)(17)(18)(19)(20)(21), and plays a predominant role in the entry of carbon into metabolism in nonphotosynthetic cells, and in determining both sink strength and phloem loading (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…The UDPGlc is converted to adenosine 5'-diphosphate glucose (ADPGlc) in the cytosol by the stepwise reactions of UDPGlc pyrophosphorylase and ADPGlc pyrophosphorylase (AGPase), while the conversion of fructose to ADPGlc involves hexokinase, phosphoglucoisomerase and phosphoglucomutase [11]. Although UDP is the preferred nucleoside diphosphate substrate for SuSy, ADP could also be an acceptor molecule of this sucrolytic enzyme to produce ADPGlc [12][13][14]. Cytosolic ADPGlc is then thought to be transported into the amyloplast by means of Brittle-1, a membrane protein located in the envelope membranes of amyloplasts [15], whose absence results in reduced starch content [16,17].…”
Section: Sucrose Synthase (Susy)mentioning
confidence: 99%
“…It starts with individual chains as the first level, which are formed by ADP-glucose through (1→4)-α-glycosidic linkages. Those chains in amylopectin have been further denoted as C chains having the reducing end, A chains (degree of polymerization, DP, [6][7][8][9][10][11][12] carrying no branches, B1 chains (DP [13][14][15][16][17][18][19][20][21][22][23][24] carrying A chains, B2 chains (DP DOI 10.1515/amylase-2017-0006 [25][26][27][28][29][30][31][32][33][34][35][36] carrying B1 chains, B3 chains (DP > 36) carrying B2 chains, and so on (for a recent review, see [2]). Although still occasionally one finds statements to the contrary, amylose is not solely linear, but contains a small but significant number of long-chain branches [3].…”
Section: Introductionmentioning
confidence: 99%